YOUTH PARTICIPATION AND ELECTORAL DEMOCRACY IN KOGI STATE; ISSUES AND PROSPECTS - MICHAEL DANIEL; DUNCAN GANYU ADAMSON (International Studies Journal)
The paper clarifies how youth political engagement in electoral democracy is understood and the activities that constitute challenges for successful democratic process in Kogi State. The paper further explains youth participation in electoral democracy and they desire for equal representation and good governance. These desire were punctuated by money politics, electoral financing and electoral violence. The electoral series held between 2015 and 2023, revealed political violence and outrageous elections expense at all tiers of electoral contest, which infiltrate to produce declared winner without integrity. It is proof that cost of registration and administration of campaigning hinder youth participation in politic. Sadly, previous empirical studies failed to indicate the derogatory implication of money politics and how has electoral expenditures overtaken the place of merit. This situation further introduces youth as instrument of destruction that crept Nigeria political event. The paper explained how this perception affects electoral integrity in Kogi State. This paper examines youth participation in electoral democracy, and how electoral expenditure has hindered youth participation in electoral democracy, a signals to poor political culture. The paper adopted descriptive methods. This approach relies on both primary and secondary sources. The primary sources rely on copies of questionnaire. Secondary sources rely on textbook, journal, conference proceeding and Nigeria daily. The study adopted Marxist theory of Democracy. The finding indicates huge electoral expenditures, political inequality and compromised political space overtaken the place merit, which restrict youths from electoral contest. The paper recommends youth sensitization on political culture, with the view to exposing the risk associated with money politics and electoral violence in Nigeria.